Floating Clouds Based on a Novel by Fumiko Hayashi - Hayashi, Fumiko (Mikio Naruse)
"Amour fou" in Tokyo. Adapted from Fumiko Hayashi's best-selling novel, Naruse's undisputed masterpiece contrasts two characters: a strong woman who relentlessly pursues her desire while hoping her lover and society will understand what she has to do to survive, and her lover who craves a conventionally validated social identity. To him, she represents a blind spot that he cannot face. They love each other, but the times are out of kilter and they are hopelessly out of synch, trying to live as individuals in a newly democratised Japan. [Cover]